Morphometric Study of the Brachial Plexus and Its Surgical Implications in Upper Limb Surgeries - Aneela Ahsan, Saira Aslam, Ahmad Farzad Qureshi, Aamer Wadud, Zubda Akhtar, Muhammad Farooq, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Precise knowledge of the morphometry and anatomical variability of the BrachialPlexus (BP) is essential to optimize surgical approaches and regional anesthesia of the upper limb. This prospective cadaveric